Pengaruh Strategi “REACT” Terhadap Literasi Kimia Peserta Didik Kelas X MIA Pada Pembelajaran Reaksi Redoks - Hadinugrahaningsih, Tritiyatma; Rosita, Rosita; Kurniadewi, Fera (LPPM Universitas Negeri Jakarta, 2019)
This study aims to determine the effect of REACT strategy on the chemical literacy of 10th grade students on learning redox reactions. The survey conducted in the even semester of the 2018/2019 academic year at one of public senior high school in Jakarta. The method used in this research was Quasi Experiment with Posttest Only Control Group Design. The sample used in this study was obtained through a purposive sampling technique to get two classes, X MIA 2 as an experimental class applied REACT strategy, and X MIA 1 as a control class applied active learning. The data was taken based on pretest and posttest score from using chemical literacy instruments. The results showed that the average posttest score of experimental class (67,324) was higher than the control class (54,030). Based on the calculation of the t-test obtained the value of count (3.827) and table (1,668) at the significance level of 5%. Therefore, the value of count > table, Then H0 is rejected and H1 is accepted. So, it can be concluded that the use of REACT strategy has a positive effect on student’s chemical literacy on redox reaction material. Keywords Chemical literacy, redox reactions, REACT strategy